The Complex Interplay between Lipids, Immune System and Interleukins in Cardio-Metabolic Diseases. - Bernardi, Stella; Marcuzzi, Annalisa; Piscianz, Elisa; Tommasini, Alberto; Fabris, Bruno (Int J Mol Sci, 2018)
Lipids and inflammation regulate each other. Early studies on this topic focused on the systemic effects that the acute inflammatory response-and interleukins-had on lipid metabolism. Today, in the era of the obesity epidemic, whose primary complications are cardio-metabolic diseases, attention has moved to the effects that the nutritional environment and lipid derangements have on peripheral tissues, where lipotoxicity leads to organ damage through an imbalance of chronic inflammatory responses. After an overview of the effects that acute inflammation has on the systemic lipid metabolism, this review will describe the lipid-induced immune responses that take place in peripheral tissues and lead to chronic cardio-metabolic diseases. Moreover, the anti-inflammatory effects of lipid lowering drugs, as well as the possibility of using anti-inflammatory agents against cardio-metabolic diseases, will be discussed.
Keywords: Anti-Inflammatory Agents; Cardiovascular Diseases; Humans; Hypolipidemic Agents; Immune System; Inflammation; Interleukins; Lipid Metabolism; Lipids; Metabolic Diseases

Neuronal Dysfunction Associated with Cholesterol Deregulation. - Marcuzzi, Annalisa; Loganes, Claudia; Valencic, Erica; Piscianz, Elisa; Monasta, Lorenzo; Bilel, Sabrine; Bortul, Roberta; Celeghini, Claudio; Zweyer, Marina; Tommasini, Alberto (Int J Mol Sci, 2018)
Cholesterol metabolism is crucial for cells and, in particular, its biosynthesis in the central nervous system occurs in situ, and its deregulation involves morphological changes that cause functional variations and trigger programmed cell death. The pathogenesis of rare diseases, such as Mevalonate Kinase Deficiency or Smith⁻Lemli⁻Opitz Syndrome, arises due to enzymatic defects in the cholesterol metabolic pathways, resulting in a shortage of downstream products. The most severe clinical manifestations of these diseases appear as neurological defects. Expanding the knowledge of this biological mechanism will be useful for identifying potential targets and preventing neuronal damage. Several studies have demonstrated that deregulation of the cholesterol pathway induces mitochondrial dysfunction as the result of respiratory chain damage. We set out to determine whether mitochondrial damage may be prevented by using protective mitochondria-targeted compounds, such as MitoQ, in a neuronal cell line treated with a statin to induce a biochemical block of the cholesterol pathway. Evidence from the literature suggests that mitochondria play a crucial role in the apoptotic mechanism secondary to blocking the cholesterol pathway. Our study shows that MitoQ, administered as a preventive agent, could counteract the cell damage induced by statins in the early stages, but its protective role fades over time.
Keywords: Anticholesteremic Agents; Cell Line, Tumor; Cholesterol; Electron Transport; Humans; Lovastatin; Mitochondria; Neurons; Neuroprotective Agents; Organophosphorus Compounds; Ubiquinone

Theophylline as a precision therapy in a young girl with PIK3R1 immunodeficiency. - Valencic, Erica; Grasso, Antonio Giacomo; Conversano, Ester; Lucafò, Marianna; Piscianz, Elisa; Gregori, Massimo; Conti, Francesca; Cancrini, Caterina; Tommasini, Alberto (J Allergy Clin Immunol Pract, 2018)

Curcumin Anti-Apoptotic Action in a Model of Intestinal Epithelial Inflammatory Damage. - Loganes, Claudia; Lega, Sara; Bramuzzo, Matteo; Vecchi Brumatti, Liza; Piscianz, Elisa; Valencic, Erica; Tommasini, Alberto; Marcuzzi, Annalisa (Nutrients, 2017)
The purpose of this study is to determine if a preventive treatment with curcumin can protect intestinal epithelial cells from inflammatory damage induced by IFNγ. To achieve this goal we have used a human intestinal epithelial cell line (HT29) treated with IFNγ to undergo apoptotic changes that can reproduce the damage of intestinal epithelia exposed to inflammatory cytokines. In this model, we measured the effect of curcumin (curcuminoid from ) added as a pre-treatment at different time intervals before stimulation with IFNγ. Curcumin administration to HT29 culture before the inflammatory stimulus IFNγ reduced the cell apoptosis rate. This effect gradually declined with the reduction of the curcumin pre-incubation time. This anti-apoptotic action by curcumin pre-treatment was paralleled by a reduction of secreted IL7 in the HT29 culture media, while there was no relevant change in the other cytokine levels. Even though curcumin pre-administration did not impact the activation of the NF-κB pathway, a slight effect on the phosphorylation of proteins in this inflammatory signaling pathway was observed. In conclusion, curcumin pre-treatment can protect intestinal cells from inflammatory damage. These results can be the basis for studying the preventive role of curcumin in inflammatory bowel diseases.
Keywords: Anti-Inflammatory Agents, Non-Steroidal; Apoptosis; Cell Survival; Curcuma; Curcumin; Cytokines; Epithelial Cells; HT29 Cells; Humans; Inflammation; Interferon-gamma; Interleukin-7; Intestinal Mucosa; NF-kappa B; Phosphorylation; Signal Transduction

Action of methotrexate and tofacitinib on directly stimulated and bystander-activated lymphocytes. - Piscianz, Elisa; Candilera, Vanessa; Valencic, Erica; Loganes, Claudia; Paron, Greta; De Iudicibus, Sara; Decorti, Giuliana; Tommasini, Alberto (Mol Med Rep, 2016)
Chronic inflammation associated with autoimmune activation is characteristic of rheumatic diseases from childhood to adulthood. In recent decades, significant improvements in the treatment of these types of disease have been achieved using disease modifying anti-rheumatic drugs (DMARDs), such as methotrexate (MTX) and, more recently, using biologic inhibitors. The recent introduction of kinase inhibitors (for example, tofacitinib; Tofa) further increases the available ARDs. However, there are patients that do not respond to any treatment strategies, for whom combination therapies are proposed. The data regarding the combined action of different drugs is lacking and the knowledge of the mechanisms of ARDs and their actions upon pathogenic lymphocytes, which are hypothesized to sustain disease, is poor. An in vitro model of inflammation was developed in the current study, in which stimulated and unstimulated lymphocytes were cultured together, but tracked separately, to investigate the action of MTX and Tofa on the two populations. By analysing lymphocyte proliferation and activation, and cytokine secretion in the culture supernatants, it was established that, due to the presence of activated cells, unstimulated cells underwent a bystander activation that was modulated by the ARDs. Additionally, varying administration schedules were demonstrated to affect lymphocytes differently in vitro, either directly or via bystander activation. Furthermore, MTX and Tofa exerted different effects; while MTX showed an antiproliferative effect, Tofa marginally effected activation, although only a slight antiproliferative action, which could be potentiated by sequential treatment with MTX. Thus, it was hypothesized that these differences may be exploited in sequential therapeutic strategies, to maximize the anti‑rheumatic effect. These findings are notable and must be accounted for, as bystander‑activated cells in vivo could contribute to the spread of autoimmune activation and disease progression.

Geranylgeraniol and Neurological Impairment: Involvement of Apoptosis and Mitochondrial Morphology. - Marcuzzi, Annalisa; Piscianz, Elisa; Zweyer, Marina; Bortul, Roberta; Loganes, Claudia; Girardelli, Martina; Baj, Gabriele; Monasta, Lorenzo; Celeghini, Claudio (Int J Mol Sci, 2016)
Deregulation of the cholesterol pathway is an anomaly observed in human diseases, many of which have in common neurological involvement and unknown pathogenesis. In this study we have used Mevalonate Kinase Deficiency (MKD) as a disease-model in order to investigate the link between the deregulation of the mevalonate pathway and the consequent neurodegeneration. The blocking of the mevalonate pathway in a neuronal cell line (Daoy), using statins or mevalonate, induced an increase in the expression of the inflammasome gene (NLRP3) and programmed cell death related to mitochondrial dysfunction. The morphology of the mitochondria changed, clearly showing the damage induced by oxidative stress and the decreased membrane potential associated with the alterations of the mitochondrial function. The co-administration of geranylgeraniol (GGOH) reduced the inflammatory marker and the damage of the mitochondria, maintaining its shape and components. Our data allow us to speculate about the mechanism by which isoprenoids are able to rescue the inflammatory marker in neuronal cells, independently from the block of the mevalonate pathway, and about the fact that cell death is mitochondria-related.

Putative modifier genes in mevalonate kinase deficiency. - Marcuzzi, Annalisa; Vozzi, Diego; Girardelli, Martina; Tricarico, Paola Maura; Knowles, Alessandra; Crovella, Sergio; Vuch, Josef; Tommasini, Alberto; Piscianz, Elisa; Bianco, Anna Monica (Mol Med Rep, 2016)
Mevalonate kinase deficiency (MKD) is an autosomal recessive auto‑inflammatory disease, caused by impairment of the mevalonate pathway. Although the molecular mechanism remains to be elucidated, there is clinical evidence suggesting that other regulatory genes may be involved in determining the phenotype. The identification of novel target genes may explain non‑homogeneous genotype‑phenotype correlations, and provide evidence in support of the hypothesis that novel regulatory genes predispose or amplify deregulation of the mevalonate pathway in this orphan disease. In the present study, DNA samples were obtained from five patients with MKD, which were then analyzed using whole exome sequencing. A missense variation in the PEX11γ gene was observed in homozygosis in P2, possibly correlating with visual blurring. The UNG rare gene variant was detected in homozygosis in P5, without correlating with a specific clinical phenotype. A number of other variants were found in the five analyzed DNA samples from the MKD patients, however no correlation with the phenotype was established. The results of the presents study suggested that further analysis, using next generation sequencing approaches, is required on a larger sample size of patients with MKD, who share the same MVK mutations and exhibit 'extreme' clinical phenotypes. As MVK mutations may be associated with MKD, the identification of specific modifier genes may assist in providing an earlier diagnosis.

Altered germinal center reaction and abnormal B cell peripheral maturation in PI3KR1-mutated patients presenting with HIGM-like phenotype. - Lougaris, Vassilios; Faletra, Flavio; Lanzi, Gaetana; Vozzi, Diego; Marcuzzi, Annalisa; Valencic, Erica; Piscianz, Elisa; Bianco, AnnaMonica; Girardelli, Martina; Baronio, Manuela; Loganes, Claudia; Fasth, Anders; et al. (Clin Immunol, 2015)
Keywords: B-Lymphocytes; Child, Preschool; Female; Germinal Center; Humans; Hyper-IgM Immunodeficiency Syndrome; Infant; Male; Mutation; Phenotype; Phosphatidylinositol 3-Kinases; RNA Splice Sites; Sequence Analysis, DNA

Knockdown of MVK does not lead to changes in NALP3 expression or activation. - Celsi, Fulvio; Piscianz, Elisa; Romano, Maurizio; Crovella, Sergio (J Inflamm (Lond), 2015)
BACKGROUND: Mutations in the Mevalonate Kinase gene (MVK) are causes of a rare autoinflammatory disease: Mevalonate Kinase Deficiency and its more acute manifestation, Mevalonic Aciduria. The latter is characterized, among other features, by neuroinflammation, developmental delay and ataxia, due to failed cerebellar development or neuronal death through chronic inflammation. Pathogenesis of neuroinflammation in Mevalonate Kinase Deficiency and Mevalonic Aciduria has not yet been completely clarified, however different research groups have been suggesting the inflammasome complex as the key factor in the disease development. A strategy to mimic this disease is blocking the mevalonate pathway, using HMG-CoA reductase inhibitors (Statins), while knock-out mice for Mevalonate Kinase are non-vital and their hemyzygous (i.e only one copy of gene preserved) littermate display almost no pathological features. FINDINGS: We sought to generate a murine cellular model closely resembling the pathogenic conditions found in vivo, by direct silencing of Mevalonate Kinase gene. Knockdown of Mevalonate Kinase in a murine microglial cellular model (BV-2 cells) results in neither augmented NALP3 expression nor increase of apoptosis. On the contrary, statin treatment of BV-2 cells produces an increase both in Mevalonate Kinase and NALP3 expression. CONCLUSIONS: MKD deficiency could be due or affected by protein accumulation leading to NALP3 activation, opening novel questions about strategies to tackle this disease.

Microglia activation and interaction with neuronal cells in a biochemical model of mevalonate kinase deficiency. - Tricarico, Paola Maura; Piscianz, Elisa; Monasta, Lorenzo; Kleiner, Giulio; Crovella, Sergio; Marcuzzi, Annalisa (Apoptosis, 2015)
Mevalonate kinase deficiency is a rare disease whose worst manifestation, characterised by severe neurologic impairment, is called mevalonic aciduria. The progressive neuronal loss associated to cell death can be studied in vitro with a simplified model based on a biochemical block of the mevalonate pathway and a subsequent inflammatory trigger. The aim of this study was to evaluate the effect of the mevalonate blocking on glial cells (BV-2) and the following effects on neuronal cells (SH-SY5Y) when the two populations were cultured together. To better understand the cross-talk between glial and neuronal cells, as it happens in vivo, BV-2 and SH-SY5Y were co-cultured in different experimental settings (alone, transwell, direct contact); the effect of mevalonate pathway biochemical block by Lovastatin, followed by LPS inflammatory trigger, were evaluated by analysing programmed cell death and mitochondrial membrane potential, cytokines' release and cells' morphology modifications. In this experimental condition, glial cells underwent an evident activation, confirmed by elevated pro-inflammatory cytokines release, typical of these disorders, and a modification in morphology. Moreover, the activation induced an increase in apoptosis. When glial cells were co-cultured with neurons, their activation caused an increase of programmed cell death also in neuronal cells, but only if the two populations were cultured in direct contact. Our findings, being aware of the limitations related to the cell models used, represent a preliminary step towards understanding the pathological and neuroinflammatory mechanisms occurring in mevalonate kinase diseases. Contact co-culture between neuronal and microglial cells seems to be a good model to study mevalonic aciduria in vitro, and to contribute to the identification of potential drugs able to block microglial activation for this orphan disease. In fact, in such a pathological condition, we demonstrated that microglial cells are activated and contribute to neuronal cell death. We can thus hypothesise that the use of microglial activation blockers could prevent this additional neuronal death.

To Extinguish the Fire from Outside the Cell or to Shutdown the Gas Valve Inside? Novel Trends in Anti-Inflammatory Therapies. - Marcuzzi, Annalisa; Piscianz, Elisa; Valencic, Erica; Monasta, Lorenzo; Vecchi Brumatti, Liza; Tommasini, Alberto (Int J Mol Sci, 2015)
Cytokines are the most important soluble mediators of inflammation. Rare pediatric diseases provided exemplar conditions to study the anti-inflammatory efficacy of new generation therapies (biologics/biopharmaceuticals) selectively targeting single cytokines. Monoclonal antibodies and recombinant proteins have revolutionized anti-inflammatory therapies in the last two decades, allowing the specific targeting of single cytokines. They are very effective in extinguishing inflammation from outside the cell, even with the risk of an excessive and prolonged immunosuppression. Small molecules can enter the cell and shutdown the valve of inflammation by directly targeting signal proteins involved in cytokine release or in response to cytokines. They are orally-administrable drugs whose dosage can be easily adjusted to obtain the desired anti-inflammatory effect. This could make these drugs more suitable for a wide range of diseases as stroke, gout, or neurological impairment, where inflammatory activation plays a pivotal role as trigger. Autoinflammatory diseases, which have previously put anti-cytokine proteins in the limelight, can again provide a valuable model to measure the real potential of small inhibitors as anti-inflammatory agents.

Fate of lymphocytes after withdrawal of tofacitinib treatment. - Piscianz, Elisa; Valencic, Erica; Cuzzoni, Eva; De Iudicibus, Sara; De Lorenzo, Elisa; Decorti, Giuliana; Tommasini, Alberto (PLoS One, 2014)
Tofacitinib (Tofa) is an inhibitor of Janus Kinase 3, developed for the treatment of autoimmune diseases and for the prevention of transplant rejection. Due to its selective action on proliferating cells, Tofa can offer a way to block T cell activation, without toxic effects on resting cells. However, few studies have investigated the effects of Tofa on lymphocyte activation in vitro. Our aim was to study the action of Tofa on different lymphocyte subsets after in vitro stimulation and to track the behaviour of treated cells after interruption of the treatment. Peripheral blood lymphocytes were stimulated in vitro with mitogen and treated with two concentrations of Tofa. After a first period in culture, cells were washed and further incubated for an additional time. Lymphocyte subsets, activation phenotype and proliferation were assessed at the different time frames. As expected, Tofa was able to reduce the activation and proliferation of lymphocytes in the first four days of treatment. In addition the drug led to a relative decrease of Natural Killer, B cells and CD8 T cells compared to CD4 T cells. However, treated cells were still viable after the first period in culture and begun to proliferate, strikingly, in a dose dependent manner when the drug was removed from the environment by replacing the culture medium. This novel data does not necessarily predict a similar behaviour in vivo, but can warn about the clinical use of this drug when a discontinuation of treatment with Tofa is considered for any reason.
Keywords: Antigens, CD; B-Lymphocytes; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Cell Proliferation; Drug Administration Schedule; Humans; Janus Kinase 3; Killer Cells, Natural; Lymphocyte Activation; Lymphocyte Count; Phytohemagglutinins; Piperidines; Primary Cell Culture; Protein Kinase Inhibitors; Pyrimidines; Pyrroles

In vivo detection of polyomaviruses JCV and SV40 in mesenchymal stem cells from human umbilical cords. - Comar, Manola; Delbue, Serena; Zanotta, Nunzia; Valencic, Erica; Piscianz, Elisa; Del Savio, Rossella; Tesser, Alessandra; Tommasini, Alberto; Ferrante, Pasquale (Pediatr Blood Cancer, 2014)
BACKGROUND: Multipotent stromal cells are present in the Wharton's jelly matrix (WJSC) of the umbilical cord and can be used as an allogeneic source of cells to treat immunological disorders. Recently it was demonstrated that adult bone marrow (BM)-derived mesenchimal stromal cells (MSC) are susceptible to infection with viruses showing potential oncogenic properties, such as the polyomavirus JC (JCV). The aim of this study was to investigate the presence of human polyomaviruses (JCV, BK Virus-BKV, SV40, and Merkel cell polyomavirus-MCPyV) in WJSC, and explore the risk of infection. PROCEDURE: MSC samples from 35 umbilical cords were investigated by quantitative Real Time PCRs for the presence of DNA sequences of JCV, BKV, SV40, and MCPyV. RESULTS: JCV DNA was detected in 1/35 (2.8%) of MSC samples, while SV40 DNA was found in 3/35 (8.6%) of the examined samples. None of the samples showed sequences of BKV and MCPyV. CONCLUSIONS: The present study demonstrates the in vivo ability of polyomaviruses to infect WJSC. Since the therapeutic approach with the WJSC has high potentiality and a more intensive use can be easily hypothesized, the need to develop consensus guidelines to detect rare viral infections in MSC is pressing.
Keywords: DNA, Viral; Female; Fetal Blood; Humans; JC Virus; Male; Mesenchymal Stromal Cells; Polyomavirus Infections; Simian virus 40; Tumor Virus Infections

Inhibition of mesenchymal stromal cells by pre-activated lymphocytes and their culture media. - Valencic, Erica; Loganes, Claudia; Cesana, Stefania; Piscianz, Elisa; Gaipa, Giuseppe; Biagi, Ettore; Tommasini, Alberto (Stem Cell Res Ther, 2014)
INTRODUCTION: Despite having a proven immunosuppressive potential in vitro, human mesenchymal stromal cells (MSCs) are reported to display variable efficacy in vivo and, in fact, their proven benefit in the clinical practice is still limited and controversial. METHODS: The interplay between clinical grade MSCs and pre-activated donor lymphocytes or selected lymphocyte subsets was studied in vitro. The kinetics of MSC growth and viability was evaluated by adhesion-dependent changes of culture plate impedance and biochemically by a colorimetric assay. Activation of natural killer (NK) cells was assessed as well, using a flow cytometry assay. RESULTS: A strong inhibition of MSC growth was rapidly induced by the addition of pre-activated lymphocytes but not of resting lymphocytes. Inhibition seems not to be attributable to a single cell population, as similar results can be obtained by depleting NK cells or by using either selected CD4+ or CD8+ lymphocytes. In addition, conditioned medium (CM) from activated lymphocytes was able to inhibit MSC growth in a dose-dependent manner. Furthermore, licensing with IFN-γ partially protected MSCs from pre-activated lymphocytes but not from their CM. These results suggest an inhibitory role of lymphocyte-activation-derived substances. However, the identification of a single molecule responsible for MSC inhibition remained elusive, even if preliminary experiments showed that ATP and, to a lesser extent, TNF-α might play a role. CONCLUSIONS: These results suggest that survival of MSCs can be affected by soluble mediators released by activated lymphocytes. Thus it can be hypothesized that MSC immunosuppressive action in vivo could be impaired by ongoing immune activation through the release of inflammatory mediators.
Keywords: CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Cell Proliferation; Cell Survival; Cells, Cultured; Coculture Techniques; Culture Media, Conditioned; Cytokines; Humans; Killer Cells, Natural; Lymphocyte Activation; Mesenchymal Stromal Cells

The p53 transcriptional pathway is preserved in ATMmutated and NOTCH1mutated chronic lymphocytic leukemias. - Athanasakis, Emmanouil; Melloni, Elisabetta; Rigolin, Gian Matteo; Agnoletto, Chiara; Voltan, Rebecca; Vozzi, Diego; Piscianz, Elisa; Segat, Ludovica; dal Monego, Simeone; Cuneo, Antonio; Secchiero, Paola; Zauli, Giorgio (Oncotarget, 2014)
By using next generation sequencing, we have analyzed 108 B chronic lymphocytic leukemia (B-CLL) patients. Among genes involved in the TP53 pathway, we found frequent mutations in ATM (n=18), TP53 (n=10) and NOTCH1 (n=10) genes, rare mutations of NOTCH2 (n=2) and CDKN1A/p21 (n=1) and no mutations in BAX, MDM2, TNFRSF10A and TNFRSF10B genes. The in vitro treatment of primary B-CLL cells with the activator of p53 Nutlin-3 induced the transcription of p53 target genes, without significant differences between the B-CLL without mutations and those harboring either ATM or NOTCH1mutations. On the other hand, the subgroup of TP53mutated B-CLL exhibited a significantly lower induction of the p53 target genes in response to Nutlin-3 as compared to the other B-CLL samples. However, among the TP53mutated B-CLL, those showing mutations in the high hot spot region of the DNA binding domain [273-280 aa] maintained a significantly higher p53-dependent transcriptional activity as compared to the other TP53mutated B-CLL samples. Since the ability to elicit a p53-dependent transcriptional activity in vitro has a positive prognostic significance, our data suggest that ATMmutated, NOTCH1mutated and surprisingly, also a subset of TP53mutated B-CLL patients might benefit from therapeutic combinations including small molecule activator of the p53 pathway.
Keywords: Aged; Aged, 80 and over; Ataxia Telangiectasia Mutated Proteins; Base Sequence; Female; Genes, p53; Humans; Leukemia, Lymphocytic, Chronic, B-Cell; Male; Models, Molecular; Molecular Sequence Data; Mutation; Receptor, Notch1; Signal Transduction; Tumor Suppressor Protein p53

Piccolipiù, a multicenter birth cohort in Italy: protocol of the study. - Farchi, Sara; Forastiere, Francesco; Vecchi Brumatti, Liza; Alviti, Sabrina; Arnofi, Antonio; Bernardini, Tommaso; Bin, Maura; Brescianini, Sonia; Colelli, Valentina; Cotichini, Rodolfo; Culasso, Martina; De Bartolo, Paolo; et al. (BMC Pediatr, 2014)
BACKGROUND: The fetal and infant life are periods of rapid development, characterized by high susceptibility to exposures. Birth cohorts provide unique opportunities to study early-life exposures in association with child development and health, as well as, with longer follow-up, the early life origin of adult diseases. Piccolipiù is an Italian birth cohort recently set up to investigate the effects of environmental exposures, parental conditions and social factors acting during pre-natal and early post-natal life on infant and child health and development. We describe here its main characteristics. METHODS/DESIGN: Piccolipiù is a prospective cohort of expected 3000 newborns, who will be recruiting in six maternity units of five Italian cities (Florence, Rome, Trieste, Turin and Viareggio) since October 2011. Mothers are contacted during pregnancy or at delivery and are offered to participate in the study. Upon acceptance, their newborns are recruited at birth and followed up until at least 18 years of age. At recruitment, the mothers donate a blood sample and complete a baseline questionnaire. Umbilical cord blood, pieces of umbilical cord and heel blood spots are also collected. Postnatal follow-up currently occurs at 6, 12, and 24 months of age using on-line or postal self administered questionnaire; further questionnaires and medical examinations are envisaged. Questionnaires collect information on several factors, including mother's and/or child's environmental exposures, anthropometric measures, reproductive factors, diet, supplements, medical history, cognitive development, mental health and socioeconomic factors. Health promotion materials are also offered to parents. DISCUSSION: Piccolipiù will broaden our understanding of the contribution of early-life factors to infant and child health and development. Several hypotheses on the developmental origins of health can be tested or piloted using the data collected from the Piccolipiù cohort. By pooling these data with those collected by other existing birth cohorts it will be possible to validate previous findings and to study rare exposures and outcomes.
Keywords: Adolescent; Child; Child Development; Child Welfare; Child, Preschool; Cohort Studies; Environmental Exposure; Humans; Infant; Infant, Newborn; Italy; Prospective Studies; Socioeconomic Factors

The effect of clodronate on a mevalonate kinase deficiency cellular model. - Zanin, Valentina; Marcuzzi, Annalisa; Piscianz, Elisa; Vuch, Josef; Bianco, Anna Monica; Monasta, Lorenzo; Decorti, Giuliana; Crovella, Sergio (Inflamm Res, 2012)
BACKGROUND: A potential anti-inflammatory effect of clodronate--an aminobisphosphonate--was described to antagonize the pro-inflammatory effects of the block in the mevalonate pathway, the main feature of a rare auto-inflammatory disease called mevalonate kinase deficiency (MKD). OBJECTIVE: In this study we evaluated the potential anti-inflammatory effect of clodronate in MKD--a still orphan drug pediatric disease. METHODS: We studied some biological parameters, nitric oxide production using Griess reagents and programmed cell death by flow cytometry, as common inflammatory parameters in MKD, in the presence of different doses of clodronate (1, 10 and 100 μM). RESULTS: In our cellular model and in monocytes from patients with MKD, clodronate induced an increase in programed cell death and nitric oxide production in comparison with non-treated cells. CONCLUSION: Our findings suggest that clodronate does not have an anti-inflammatory effect as previously reported but that it increases the epiphenomena of this pediatric disease.
Keywords: Adolescent; Adult; Alendronate; Animals; Anti-Inflammatory Agents; Apoptosis; Cell Line; Cells, Cultured; Child; Clodronic Acid; Female; Humans; Inflammation; Lipopolysaccharides; Male; Mevalonate Kinase Deficiency; Mice; Models, Biological; Monocytes; Nitric Oxide; Young Adult

From bone marrow transplantation to cellular therapies: possible therapeutic strategies in managing autoimmune disorders. - Taddio, Andrea; Biondi, Andrea; Piscianz, Elisa; Valencic, Erica; Biagi, Ettore; Badolato, Raffaele (Curr Pharm Des, 2012)
Chronic inflammatory disorders occurring in childhood represent a serious therapeutic challenge. However, available therapies seem not to be targeted on the pathogenic mechanism of the disease and are often not actively affecting the natural history of the disease. Emerging treatments might be of some benefit to many patients who did not respond to conventional therapeutic options. Biological therapies with monoclonal antibodies and other recombinant proteins have been introduced in clinical practice. At the same time, mesenchymal stromal cells (MSC) have gained attention as a savage treatment in patients subjected to hematopoietic stem cell transplantation who develop severe graft versus host disease (GvHD); in addition, recent reports from clinical trials on larger cohorts of patients support their use as second-line treatment after failure of corticosteroid treatment. For analogy, they have been proposed for the treatment of intractable autoimmune disorders. Hematopoietic stem cell transplantation (HSCT) has been shown to be effective for treatment of rheumatic disorder cases that were resistant to traditional therapies especially if combined with cell manipulation techniques, such as selection of regulatory T cell and depletion of harmful lymphocytes. We herein present the rationale of different strategies, the preliminary data obtained in clinical trials, unsolved problems and possible next developments of novel treatment protocols of autoimmune disorders.
Keywords: Autoimmune Diseases; Bone Marrow Transplantation; Child; Chronic Disease; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; Humans; Inflammation; Lymphocytes; Mesenchymal Stem Cell Transplantation; T-Lymphocytes, Regulatory; Treatment Outcome

Immunomodulatory drugs in autoimmune lymphoproliferative syndrome (ALPS). - Tommasini, Alberto; Valencic, Erica; Piscianz, Elisa; Rabusin, Marco (Pediatr Blood Cancer, 2012)
Keywords: Antineoplastic Agents; Autoimmune Lymphoproliferative Syndrome; Diseases in Twins; Humans; Male; Pentostatin

Lovastatin-induced apoptosis is modulated by geranylgeraniol in a neuroblastoma cell line. - Marcuzzi, Annalisa; Zanin, Valentina; Piscianz, Elisa; Tricarico, Paola Maura; Vuch, Josef; Girardelli, Martina; Monasta, Lorenzo; Bianco, Anna Monica; Crovella, Sergio (Int J Dev Neurosci, 2012)
Mevalonic aciduria (MA), the most severe form of mevalonate kinase deficiency (MKD), is still an orphan drug disease and the pathogenetic mechanisms underlying neuronal dysfunction is still poorly understood. In our study we have investigated the apoptotic mechanism mediated by the exposure of the cultured neuroblastoma cell line, SH-SY5Y, to lovastatin in absence or in presence of the isoprenoid, geranylgeraniol, with the aim of unraveling the pathogenesis of MA. Lovastatin, blocks the mevalonate pathway inhibiting the 3-hydroxy-3-methylglutaryl-CoA reductase (HMG-CR), an enzyme of the mevalonate pathway upstream the mevalonate kinase enzyme, reproducing biochemical features similar to those found in MKD. We demonstrate that apoptosis in neuronal lovastatin treated-cells is induced by the mitochondrial pathway, with caspase-9 as the initiator and caspase-3 as the effector caspase. The presence of geranylgeraniol modulates both the caspase-9 and caspase-3 activity in a dose-dependent way, confirming that this isoprenoid enters the mevalonate pathway, is metabolized and finally is able to by-pass the statin biochemical block reconstituting the mevalonate pathway. According to our findings, it should not be the time course adopted that modulates the apoptotic response but rather the isoprenoid itself. Being aware that our results have been obtained using a biochemical model of MKD, and not cells from patients with the disease, we believe our findings increase the knowledge of MA pathogenesis, and may possibly contribute to the development of novel therapeutic strategies.
Keywords: Analysis of Variance; Apoptosis; Caspases; Cell Line, Tumor; Diterpenes; Dose-Response Relationship, Drug; Drug Interactions; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Lovastatin; Neuroblastoma; Time Factors

Differential action of 3-hydroxyanthranilic acid on viability and activation of stimulated lymphocytes. - Piscianz, Elisa; Cuzzoni, Eva; De Iudicibus, Sara; Valencic, Erica; Decorti, Giuliana; Tommasini, Alberto (Int Immunopharmacol, 2011)
Lymphocytes proliferation after antigen-driven activation leads to an increase in cell count, which could last some week, until apoptosis mechanisms allow the homeostatic control of the system. During the first days of this stimulation, activated lymphocytes display high resistance to apoptosis and to most immunosuppressive drugs. According to the literature, few compounds have been described to kill recently activated cells, by inhibiting metabolic processes fundamental to proliferation. The aim of our work was to evaluate comparatively these different compounds, in order to identify the best strategy to kill cells that have undergone proliferation, while sparing the repertoire of resting cells. After preliminary experiments, 3-HAA and bortezomib were selected as the most suitable compounds for our purposes. The possible synergic effect of 3-HAA with bortezomib or with manganese ions was also assessed. 3-HAA was confirmed to be the most reliable pharmacologic approach to inhibit proliferation with acceptable toxicity on resting cells. While in the case of PHA stimulation 3-HAA led to death of most lymphocytes, only a minor percentage of cells were killed after allo-stimulation, suggesting that the effect is proportional to the percentage of stimulated lymphocytes. Manganese ions further enhanced this effect, while results with bortezomib seemed to be less consistent. These results deserve further investigations to develop new procedures for targeting activated cells with pharmacological approaches.
Keywords: 3-Hydroxyanthranilic Acid; Boronic Acids; Cell Survival; Cells, Cultured; Humans; Lymphocyte Activation; Lymphocytes; Manganese; Pyrazines